A study on Children's Learning Evaluation in Macao Kindergarten——Taking a Kindergarten in Macao as an example =: 澳門幼師對幼兒學習評量之研究——以澳門某幼稚園為例 - Chan Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Study of Using Game-Based Learning into English Learning to Improve the Lerning Outcomes of Primary Level Students in Macau =: 遊戲式教學融入澳門小學低年級英語課程以提升學生學習成效之行動研究 - Hsu, Hsiao Chien (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge and Attitude of Parents with Regular Primary Children Towards Inclusive Education in Macau =: 澳門小學普通生家長對澳門融合教育的認識及態度之調查報告 - Chong, Leng Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Macau Secondary School Teachers’ Attitudes Towards Inclusive Education and Concern Over It =: 澳門中學教師對融合教育的態度與憂慮之研究 - 陳瀅瀅 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Challenges of Nursery Teachers in the Early Childhood Inclusion Classes: A Qualitative Study of Macao Nursery Teachers - Wu, Ma Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Trying a board game intervention on children with autism spectrum disorder in Macau: how do they react? - Lok, Ka Ieong; Chiang, Hsu-Min; Lin, Yueh-Hsien; Jiang, Chunlian (International Journal of Developmental Disabilities, 2022)
Limited special education and related services are available for children with autism spectrum disorder (ASD) in Macau, especially those who are educated in general education classrooms. No intervention study has been conducted on these children. This study was conducted to explore the relationship between a board game play intervention and board game play behaviors and social communication of children with ASD educated in general education classrooms in Macau. A repeated measures design was used and the results of this study showed the mean occurrence of unprompted board game play behaviors per session during intervention was not significantly different from that during pre- or post-intervention. The mean occurrence of social communication per session during intervention was significantly higher than that during pre- and post-intervention. These findings suggest a positive relationship existed between the board game intervention used in this study and social communication of children with ASD.
Keywords: Autism Spectrum Disorder; Macau; board game; play; social communication

初中教師面對融合學生校園欺凌經驗及應對策略之研究 =: Research on the Experience and Coping Stratrgies of Junior High School Teachers in the Face of Integrated Students' Bullying in Schools - Cheok, Pou Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

探討第29/2020號行政法規對特殊教育教師為特殊需求學生評估的影響 =: Exploring the impact of Administrative Regulation No. 29/2020 on the evalution of the special education teachers for students with special needs - Lo, Chon In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育